The decline of water consumption in Spanish cities: structural and contingent factors. Issue 6 (1st November 2020) - Sauri, David
ABSTRACT: As cities will concentrate most of the world's population and economic activities, so urban water demand will account for a large proportion of global water demand in the future. In contrast, recent empirical evidence indicates that water consumption in many cities of the developed world is declining. In this article, this decline in consumption is studied for the major Spanish cities, and some of the drivers of this decline (economic, technological and behavioural) are explored. Contingent events such as droughts and economic crises may intensify the decline in consumption, as shown for the case of Barcelona.